(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article is about the efficient generation of electrical energy and its use. The generators known to this day had the appropriate efficiency and the consumer was satisfied with this. The development of science and technology has made it possible to increase the efficiency of electricity generation by connecting solar panels and wind turbines to the battery. The main element of this circuit is a device called an inverter. The article describes the definition of an inverter, its operating principle, types and methods of application. Architects and designers working on the construction of dwellings and premises, having knowledge about electrical installation of this level, will certainly achieve the desired result.